Cultural Evaluation of “Let’s Learn Persian” and “Top Notch” Series as a Foreign Language: Based on Hatoss’ Comprehensive Model - Gholamhossein Shahini; Mojtaba Nazari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Given the role culture plays in second/foreign language learning, paying attention to cultural content in language teaching textbooks is of great importance. In the current study, using qualitative content analysis, the way cultural issues are presented in the first three volumes of the two series of Let’s Learn Persian and Top Notch was evaluated based on 20 questions in Hatoss’ cultural model. The findings indicate that “Top Notch” series showed a better performance than “Let’s Learn Persian” series in reflecting cultural pluralism, cultural dynamicity, up-to-date cultural norms, explicit and direct teaching of cultural norms, and inviting L2 learners to ponder over cultural norms. Moreover, issues like pragmatic competence, non-linguistic inputs, semiotics, and deep and surface culture were similarly treated in the two series. Besides, abstract cultural issues were not dealt with in the two series and the prevalent teaching method was cognitive than experiential. And finally, given the introduction of different cultures, intercultural communications are mirrored more in “Top Notch” than “Let’s Learn Persian”.